Evolutionary and functional significance of lengthy copulations in a promiscuous apple snail, Pomacea canaliculata (Caenogastropoda: Ampullariidae) - Burela, Silvana (2011)
The peculiar adaptations of the dioecious freshwater snails belonging to the family Ampullariidae have recently been recognized as important, albeit neglected, models for evolutionary ecology studies. A review of the literature, mostly reports from unsystematic observations under laboratory conditions, revealed considerable variation (38 min to 20 h) in the duration of copulation in this family, both at inter- and intraspecific levels. The aims of our study were to investigate if the lengthy copulations of Pomacea canaliculata occur naturally in the wild and if a significant part of the copulation duration was to accomplish genital connection or to impede the access of other males, rather than being necessary solely for sperm transfer. The effect of single vs repeated copulations in terms of female reproductive output, and the effect of some proximate factors (male size, mating status, time of the day and prowler males) on the duration of copulation were also evaluated. Our field results indicate that lengthy copulations previously reported for P. canaliculata were not an artefact. The laboratory evidence obtained indicates that the completion of the genital connection or a preinsemination mate guarding can account for only 20 of the copulatory period and that there is no postinsemination guarding. Most of the copulation time is apparently necessary to transfer an amount of sperm that will ensure the fertilization of the thousands of ova produced during the entire lifetime of females. Our laboratory experiments also showed that there was no effect of male size, the time at which copulation began, the mating status of snails or of the presence of prowler males on the duration of copulation. © 2010 The Author. Published by Oxford University Press on behalf of The Malacological Society of London, all rights reserved.